2013
DOI: 10.1080/19440049.2013.849007
|View full text |Cite
|
Sign up to set email alerts
|

Mycobiota and toxigenic Penicillium species on two Spanish dry-cured ham manufacturing plants

Abstract: The present study reports the natural mycobiota occurring in dry-cured hams, and in particular on the incidence of mycotoxin-producing fungi. A total of 338 fungal colonies were isolated from three stages of production, these being the post-salting, ripening and aging stages in two manufacturing plants. The results show that fungi were more frequently isolated from the aging stage and that the predominant filamentous fungal genus isolated was Penicillium. Seventy-four of the 338 fungal strains were selected fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 44 publications
(64 reference statements)
2
30
0
Order By: Relevance
“…Starter strains should not be able to produce neither mycotoxins nor antibiotics. Therefore, although these strains were unable to produce CPA and/or OTA (Alapont et al 2014), further studies should be conducted to analyze the ability of these selected strains to produce other mycotoxins and antibiotics…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Starter strains should not be able to produce neither mycotoxins nor antibiotics. Therefore, although these strains were unable to produce CPA and/or OTA (Alapont et al 2014), further studies should be conducted to analyze the ability of these selected strains to produce other mycotoxins and antibiotics…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this fact should be taken into account for its use as starter culture. In this regard, P. commune strains KC009764, KC009778, KC009786, KC009806, KC0099816, KC00928, KC009812 and KC009767 were not able to produced neither OTA nor CPA (Alapont et al 2014), of which KC0099816 and KC009786 strains showed the higher activity against oleic and lauric acids (halo size>10 mm).…”
Section: Proteolytic Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…The hygienic quality of raw materials, the manufacturing practices and the environmental factors (such as temperature and relative humidity) during ripening determine the type and growth rate of fungi growing on the surface of dry-cured meats. A complex mycobiota is generally observed on the surface of these products with Aspergillus, Eurotium and Penicillium as the most frequently isolated genera (Comi et al 2004;Samson et al 2004a;Battilani et al 2007;Sørensen et al 2008;Sonjak et al 2011;Alapont et al 2014). These fungi are generally assumed to improve taste and quality, due to their lipolytic and proteolytic activities (Ludemann et al 2004;Martín et al 2004Martín et al , 2006Sonjak et al 2011).…”
Section: Introductionmentioning
confidence: 99%